Pharmacotherapy literacy questionnaire for parents of pre-school children in Serbia: Construction and psychometric characteristics - Ubavić Stana; Krajnović Dušanka; Bogavac-Stanojević Nataša (Vojnosanitetski Pregled)
Background/Aim. Valid and reliable instruments were emphasized in the studies of pharmacotherapy literacy which is the capacity to obtain, evaluate, calculate, and comprehend basic information about pharmacotherapy and actions necessary to make appropriate medication-related decisions. The aims of this study were: to develop an instrument for assessment of pharmacotherapy health literacy among parents of pre-school children in Serbia (PTHL-SR) and to evaluate psychometric properties. Methods. This study was a four-stage methodological one, conducted from November 2015 to October 2016. The instrument content was established through qualitative and quantitative expert reviews in the first and second phase. Experts had to answer about the clarity and relevance of questions. The Content Validity Ratio (CVR) and index (CVI) were calculated based on the necessity and relevance of questions. Third phase was pre-testing of initial instrument to assess comprehensibility of questions. In the fourth phase, 300 parents completed questionnaire at several kindergartens in Belgrade, to determine questionnaire’s reliability through internal consistency, using the Cronbach’s alpha coefficient and correlation between classes. Results. The 14-items questionnaire was developed (initial PTHL-SR) and pre-tested on a pilot sample. It had 4 groups of questions about knowledge, understanding, numerical skills and access to medicines-related information. The Content Validity Ratio (CVR = 0.875) was significant and adequate (Lawshe CVR8 = 0.780). Conclusion. PTHL-SR is a reliable instrument for assessment of pharmacotherapy literacy among parents of pre-school children in Serbia and can be used for the evaluation of understanding, calculating and accessing medicines-related information. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 41004]